2010
DOI: 10.3923/pjbs.2010.527.536
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Evoked Potential for Detection of Subclinical Neuropathy in Egyptian Children with Acute Lymphoblastic Leukaemia

Abstract: To evaluate neurological changes developing during paediatric Acute Lymphoblastic Leukaemia (ALL) therapy clinically and through electrophysiological Study of Somatosensory Evoked Potentials (SSEPs) changes in different phases of therapy. Thirty five-ALL patients with age range from 3-14 years were included compared to 30 healthy controls. History, neurological examination, complete blood counts, cytological examination of bone marrow aspirate and cerebrospinal fluid with Measurement of Serum Methotrexate (MTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…First, the analyzed patient groups differed in terms of age. However, it has been shown that age is not a significant factor modulating EP [26]. Second, in our study we analyzed asymptomatic patients.…”
Section: Discussionmentioning
confidence: 96%
“…First, the analyzed patient groups differed in terms of age. However, it has been shown that age is not a significant factor modulating EP [26]. Second, in our study we analyzed asymptomatic patients.…”
Section: Discussionmentioning
confidence: 96%
“…First, the analyzed patient groups differed in terms of age. However, it has been shown that age is not a signi cant factor modulating EP [23]. Second, in our study we analyzed asymptomatic patients.…”
Section: Discussionmentioning
confidence: 96%